Kingdom of the Netherlands-Aruba : 2021 Article IV Consultation Discussions-Press Release; Staff Report; and Staff Supplement. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2021)
Aruba managed to contain the pandemic in the first months of the outbreak but experienced a resurgence of new infections in the summer. The economic impact of COVID-19 is particularly severe given Aruba's high dependency on tourism. While the authorities' swift response has helped contain the human and economic damage, it could not avoid a severe GDP contraction.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet